The Role of the State in the Formation of Moderate Islam in Indonesia - Angga Yudhiyansyah (Jurnal Sosiologi Agama, 2014)
This paper examines the role of state in shaping the notion of moderate Islam in Indonesia within the context of responding to the rise of terrorism. The aftermath of Suharto’s authoritarian regime, Indonesia faces the threat of terrorist attacks from within and outside the country span from 9/11 bombing in the US to Bali bombings. Those aforementioned events have shaped the state behaviors toward Islam in Indonesia. In this regard, the notion of moderate Islam is more than just a theological or political preference. It is a notion that emerges from the context of eradicating terrorist threat. This paper argues that the massive events of terrorist attacks in home and abroad have created condition where the state has come up with the notion of moderate Islam not only as a means of inclusions for Muslim groups but also to acquire “legitimacy” for the project of counter-terrorism run by the state. Current studies on Islam and the state have undermined the role of the state in appropriating the notion of moderate Islam. Additionally, studies on Islam in Indonesia whether it is seen as theological or political preferences is captured from below meaning that Muslim society is conceived as such (radical, moderate, conservative and so forth). This study investigates the state’s programs such as Inter-religious dialogue, Seminars, establishing Muslim groups of anti-terrorism, and issuing fatwa on terrorism by MUI.